Cementation and porosity evolution of tight sandstone reservoirs in the Permian Sulige gas field, Ordos Basin (central China). (May 2019) - Fan, Aiping; Yang, Renchao; Lenhardt, Nils; Wang, Meng; Han, Zuozhen; Li, Jinbu; Li, Yijun; Zhao, Zhongjun
Abstract: Tight sandstone gas reservoirs constitute an important type of unconventional gas resources and may be of crucial significance as environment-friendly source of energy in the world. However, the dynamics of densification and evolution of the low-porosity and low-permeability sandstone reservoirs are intensively debated in literature. Recently, the question of sequence of reservoir densification and hydrocarbon accumulation has arisen. A typical tight sandstone reservoir (the first member of the Shanxi Formation and the eighth member of Shihezi Formation) in the Permian Sulige gas field in Central China provides an excellent case study to probe these questions. By using a variety of different methodologies such as scanning electron microscopy (SEM), X-ray diffraction (XRD), cathodoluminescence, fluid inclusion analysis and confocal Raman spectrometer analysis, we identified different authigenic minerals such as illite, kaolinite, dickite, chlorite and smectite illitization coexisting with siliceous and calcitic cements. These authigenic minerals precipitated at different diagenetic stages, related to the changing conditions during compaction and lithification, and therefore, changed the porosities of the host rocks during each of these stages. The types of pores in the Sulige gas field are dominated by illite and kaolinite intercrystalline pores, matrix solution pores, and primary intergranular pores. The results of this study suggest that compaction and cementation are the reasons for the most distinct loss in porosity. On the other hand, kaolinite and illite preserve their intercrystalline pores, which could be identified as the main reserve space of the tight gas reservoirs. Therefore, the secondary porosity of the sandstone reservoirs forms the most important contributor to the gas reservoir potential in the Sulige gas field. In addition, it could be inferred that the tight gas accumulation took place during the densification of the reservoirs. The implications of the presented results may also help to understand the formation of other tight reservoirs world-wide. Graphical abstract: Image 1 Highlights: First description of the sequential order of authigenic mineral formation. The secondary porosity forms the main contributor for the reservoir potential. Tight gas accumulation took place concomitant with densification of the reservoir.